Principles of public speaking - German, Kathleen M. (New York : Pearson Education, Inc, 2013)
"Balancing skills and theory, this introductory public speaking textbook encourages the reader to see public speaking as a way to build community in today's diverse world. Within a framework that emphasizes speaker responsibility, listening, and cultural awareness, this classic book uses examples from college, workplace, political, and social communication to make the study of public speaking relevant, contemporary, and exciting. This new edition includes expanded coverage of mediated speaking with examples from podcasts and online speaking contexts; discussion of ethical issues of contemporary public discourse, including disinformation and public civility; and tips for extemporaneous speaking. This textbook is ideal for general courses on public speaking as well as specialized programs in business, management, political communication, and public affairs. A companion website including an instructor's manual containing discussion questions, exercises, quiz questions, and suggestions for syllabus design is available at https://routledgetextbooks.com/textbooks/9780367860288"--
Revised edition of Principles of public speaking, 2017.
Includes bibliographical references and index.
Keywords: Public speaking